Hubungan Aktivitas Fisik dengan Tingkat Stres pada Mahasiswa Kedokteran Universitas Tarumanagara Angkatan 2022–2023 - Hamzah Hamzah; Susy Olivia Lontoh (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Stress is a common mental health problem among medical students due to academic demands. Physical activity is known to reduce stress through physiological and psychological mechanisms. This study aims to examine the relationship between physical activity and stress levels among medical students at Tarumanagara University class of 2022–2023. This research employed an analytical cross-sectional design. A total of 123 respondents who met the inclusion criteria completed the physical activity (Baecke Questionnaire) and stress level (Perceived Stress Scale-10) questionnaires. Bivariate analysis was conducted using the chi-square test. The results showed that 95.1% of respondents experienced moderate to severe stress, while only 15.4% regularly exercised. A significant relationship was found between physical activity and stress level (p = 0.000). The odds ratio of 13.600 indicates that students who exercised regularly were 13 times more likely to experience lower stress compared to those who did not. This study highlights the role of regular physical activity as a protective factor in managing stress among medical students